FACTORS AFFECTING THE QUALITY OF ONLINE RELATIONSHIPS AND ITS CONSEQUENCES ON SHOPEE AND LAZADA E-MARKETPLACE CUSTOMERS - Gugyh Susandy; Reni Dian Octaviani; Diana Sari; Dinar Hoerun Nisa (STIESA Press, 2022)
The purpose of this study is to test a model to predict antecedents and consequences of relationship quality in online purchases. Novelty: The importance of this research for the online community is to provide a series of the quality of online relationships factors and the consequences for the quality of online relationships so that e-marketplaces can choose suitable guidelines to maintain their relationships with online customers and ultimately gain customer participation in creating value and strengthen competitive status. Research Methods: This research used explanatory survey method. The hypothesis was tested using the Partial Significance Test. Finding/Results: The results showed that the online system quality and social ties have a positive effect on the online relationships quality. While the results of the research variables of online service quality, online information quality, financial influence, structural ties and vendor reputation have no influence on the online relationships quality. The results also show that the online relationships quality has a positive effect on electronic word of mouth, online customer loyalty, and online customer reviews. Limitations / implications in this research, the online relationships quality is considered a construct that includes trust, commitment and satisfaction with the relationship. However, to achieve more accurate results, further researchers can investigate the separate impact of each dimension of relationship quality (commitment, trust, and satisfaction).